Supramolecular Amino Acid Based Hydrogels: Probing the Contribution of Additive Molecules using NMR Spectroscopy. Issue 33 (23rd May 2017) - Ramalhete, Susana M.; Nartowski, Karol P.; Sarathchandra, Nichola; Foster, Jamie S.; Round, Andrew N.; Angulo, Jesús; Lloyd, Gareth O.; Khimyak, Yaroslav Z.
Abstract: Supramolecular hydrogels are composed of self‐assembled solid networks that restrict the flow of water.l ‐Phenylalanine is the smallest molecule reported to date to form gel networks in water, and it is of particular interest due to its crystalline gel state. Single and multi‐component hydrogels ofl ‐phenylalanine are used herein as model materials to develop an NMR‐based analytical approach to gain insight into the mechanisms of supramolecular gelation. Structure and composition of the gel fibres were probed using PXRD, solid‐state NMR experiments and microscopic techniques. Solution‐state NMR studies probed the properties of free gelator molecules in an equilibrium with bound molecules. The dynamics of exchange at the gel/solution interfaces was investigated further using high‐resolution magic angle spinning (HR‐MAS) and saturation transfer difference (STD) NMR experiments. This approach allowed the identification of which additive molecules contributed in modifying the material properties. Abstract : Unravelling hierarchical self‐assembly : The heterogeneous nature of supramolecular hydrogels makes them challenging materials for structure characterisation. The combination of microscopy, rheology, diffraction and advanced NMR spectroscopy methods probe the variable length scales and dynamics present in these soft materials (see picture).